A GWAS of angiotensin-converting enzyme inhibitor-induced angioedema in a South African population - Jacquiline W. Mugo, PhD; Cascia Day, Cert Allergy (Phys); Ananyo Choudhury, PhD; Maria Deetlefs, Dip Allergy (SA); Robert Freercks, MPhil; Sian Geraty, MMed; Angelica Panieri, MBChB; Christian Cotchobos, MBChB; Melissa Ribeiro, MBChB; Adelein Engelbrecht, MMed; Lisa K. Micklesfield, PhD; Michèle Ramsay, PhD; et al. (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Angiotensin-converting enzyme inhibitor–induced angioedema (AE-ACEI) is a life-threatening adverse event; globally, it is the most common cause of emergency presentations with angioedema. Several genome-wide association studies (GWASs) have found genomic associations with AE-ACEI. However, despite African Americans having a 5-fold increased risk of AE-ACEI, there are no published GWASs from Africa. Objective: The aim of this study was to conduct a GWAS of AE-ACEI in a South African population and perform a meta-analysis with an African American and European American population. Methods: The GWAS included 202 South African adults with a history of AE-ACEI and 513 controls without angioedema following angiotensin-converting enzyme inhibitor (ACEI) treatment for at least 2 years. A meta-analysis was conducted with GWAS summary statistics from an African American and European American cohort (from the Vanderbilt-Marshfield cohort, which consisted of 174 case patients and 489 controls). Results: No single-nucleotide polymorphisms (SNPs) attained genome-wide significance; however, 26 SNPs in the postimputation standard GWAS of the South African cohort and 73 SNPs in the meta-analysis attained suggestive thresholds (P < 5.0 × 10−06). Some of these SNPs were found to be located close to the genes PRKCQ (protein kinase C theta), RAD51B (RAD51 Paralog B), and RIMS1 (regulating synaptic membrane exocytosis 1), which were previously linked with drug-induced angioedema, and also close to the CSMD1 (CUB and sushi multiple domains 1) gene, which has been linked to ACEI cough, providing replication at the gene level but with novel lead SNPs. The study also replicated SNP rs500766 on chromosome 10, which was previously found to be associated with AE-ACEI. Conclusions: Our results highlight the importance of African populations for detection of novel variants in replication studies. Further increased sampling across the continent and matched functional work are needed to confirm the importance of genetic variation in understanding the biology of AE-ACEI.